E-Money Based Boarding School Cooperative Development Model (Kopontren) As An Sharia Economic Acceleration Effort In Indonesia - Marwini Marwini; Annisa Nur Salam (AL-ARBAH: Journal of Islamic Finance and Banking, 2020)
AbstractPurpose - This research aims to know E-money based boarding school cooperative (Kopontren) development models.Method - This research is used descriptive qualitative by discussing the development of the co-model with sharia economic agreements and e-money as a transaction tool.Result - The results of the research showed three models, namely development model of Islamic boarding school cooperative (Kopontren) as community economy developer, model of sharia agreement implementation in Kopontren operations, and e-money application as transaction media in Kopontren business unit.Implication - This study uses the data from the study of literature.Originality- The paper looks into the development model of the co-op with e-money based. Previous studies have only focused on development models. This paper contributes to introducing the application of an inclusive financial system.